Potential use of PGPR based biofertilizer for improving the nutrient availability in soil and agronomic efficiency of upland rice - Rahma Tia Harahap; Diyan Herdiyantoro; Mieke Rochimi Setiawati; Isna Niar Rahmatul Azizah; Tualar Simarmata (Universitas Padjadjaran, 2022)
AbstractPresent study aimed to perform literature review to investigate the current status and potential use of plant growth promoting rhizobacteria (PGPR) for enhancing the soil plant’s health, plant growth and productivity in sustainable ways. The Systematic Literature Review (SLR) methods was applied according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) on published scientific literature from 2012-2022. Results revealed that genus diversity of PGPR (Bacillus sp., Serratia sp., Streptomyces sp., Pseudomonas sp., and Burkholderia sp.) produce siderophore and phytohormones such as indole-3-acetic acid (IAA), gibberellin (GAs), auxin, and 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase activity, organic acids, biocontrol agent that contribute to the improvement of nutrient bioavailability (nitrogen fixing, phosphate solubilizing and Fe-uptake). The growth character of rice inoculated with biofertilizer and combined with 50% inorganic fertilizer produced no significant difference with pots that received 100% inorganic fertilizer. These results concluded that PGPR that produced phytohormone and siderophore could be developed as a potential bioagent or biofertilizer to improve the growth character and yield of upland rice (Oryza sativa L.) in dry environmental conditions.Keywords: PGPR producing phytohormone and siderophore, N2-fixer, Biofertilizer, Systematic review AbstrakKajian tinjauan pustaka ini dilakukan untuk menyelidiki status saat ini dan potensi penggunaan rizobakteri pemacu pertumbuhan tanaman (PGPR) untuk meningkatkan kesehatan tanah, pertumbuhan tanaman, dan produktivitas secara berkelanjutan. Metode Systematic Literature Review (SLR) diterapkan sesuai dengan Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) pada literatur ilmiah yang diterbitkan dari 2012-2022. Mesin pencari Google Scholar dan ScienceDirect dengan kata kunci yang tepat digunakan untuk memilih dan mengumpulkan jurnal ilmiah yang terindeks bereputasi dan digunakan sebagai referensi utama database. Hasil penelitian menunjukkan bahwa keragaman genus PGPR (Bacillus sp., Serratia sp., Streptomyces sp., Pseudomonas sp., dan Burkholderia sp.) menghasilkan siderophore dan memproduksi phytohormon seperti indole-3-acetic acid (IAA), giberelin (GAs), auksin, dan 1-aminocyclopropane-1-carboxylic acid (ACC) aktivitas deaminase, asam organik, agen biokontrol yang berkontribusi pada peningkatan bioavailabilitas nutrisi (pengikatan nitrogen, pelarutan fosfat, dan penyerapan Fe). Karakter tumbuh padi yang diinokulasi pupuk hayati dan dikombinasikan dengan pupuk kimia dosis 50% menghasilkan perbedaan yang tidak nyata dengan pot yang menerima pupuk anorganik 100%. Hasil ini menyimpulkan bahwa PGPR penghasil pitohormon dan siderophore dapat dikembangkan sebagai bioagent atau pupuk hayati yang potensial untuk meningkatkan karakter tumbuh dan hasil padi (Oryza sativa L.) gogo pada kondisi lingkungan yang kering.Keywords: PGPR produksi fitohormon dan siderofor, penambat-N2-fixer, biofertilizer, Systematic review